Pengaruh Implementasi Kebijakan Pendidikan dan Transformasi Budaya Organisasi terhadap Manajemen Sekolah untuk Mewujudkan Efektivitas Penggunaan Budaya Sharing di Lingkungan Pendidikan - Mulyaningsih Mulyaningsih (Akademi Sekretari Manajemen Taruna Bakti, 2017)
The quality of an education cannot be separated from the various factors that support the achievement of a good education including the existence of biased policy of government regulation that can be applied in the educational environment as a public institution. The problem of education in Indonesian society today is the high level of inefficiency. The purpose of this study is to examine the phenomenon of the problem of implementation of organizational culture transformation of the school management to realize the effectiveness of the use of sharing culture in the education environment. The object of this study is the Head of Administration at State Junior High School in West Java, with a sample of 135 people using descriptive research methods and verification through path analysis techniques (Path). The result of the research on the influence the policy planning on school management is higher than the effect of organizational culture transformation on school management, and the effect of organizational culture transformation on school management to realize the effectiveness of the use of culture sharing is simultaneously significant. Thus, in this research, the transformation of organizational culture planning must be the main priority to realizing the effectiveness of the use of sharing culture, it is necessary that the value of noble for education in Indonesia effectiveness in the use of funds issued by the Government, should be the transformation of culture sharing the same noble values - with mutual assistance in planning activities and school budgets that have been prepared that refer to the vision and mission, are equally in harmony to account for the expenditure of education funds in the form of reports in a transparent manner, equally faithful to carry out planned activities and report any funds issued transparently. Keywords: Transformation, Sharing, Policy, Education, Effectiveness